Photoluminescence, radioluminescence and thermoluminescence properties of Eu3+ doped cadmium tantalate phosphor - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2018)
For investigate spectroscopic properties, Eu3+ doped columbite type CdTa2O6 phosphors were synthesized using the solid state reaction method. The synthesized ceramic phosphors were investigated by X-ray diffraction (XRD), scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), photoluminescence (PL), radioluminescence (RL) and thermoluminescence (TL) analyses. CdTa2O6:Eu3+ phosphors exhibited emissions at 591.8 nm and 612.1 nm because of the characteristic band transitions of the Eu3+ ion. Phosphor emission increased with increasing Eu3+ ion dopant up to 1.5 mol%, and then decreased owing to concentration quenching. The decay times decreased with increasing Eu3+ dopant, while they were varied from 711 to 534 m. The scintillation emissions of Eu3+ doped samples from the UV to near-IR spectral region were monitored by RL measurements. The high RL emission may be attributed to the good scintillation property of phosphor. TL glow curves were monitored for different Eu3+ concentrations in the range of 50 degrees C to 400 degrees C at a heating rate of 2 degrees C s(-1), after being irradiated under short-wave UV light (254 nm).
Keywords: GOODNESS-OF-FIT; ENERGY-TRANSFER; SCINTILLATION PROPERTIES; CHARGE COMPENSATION; QUANTUM DOTS; THIN-FILMS; LUMINESCENCE; BEHAVIOR; CRYSTAL; DY3+